ISLAM MULTIKULTURAL: Hikmah, Tujuan, dan Keanekaragaman dalam Islam - Mujiburrahman, Mujiburrahman (ADDIN, 2013)
MULTICULTURAL ISLAM: LESSONS, OBJECTIVES, AND DIVERSITY IN ISLAM. Multiculturalism is a major challenge faced by religions in todays world, given any real religion emerged from the religious and cultural plurality. Indonesia has one of the worlds most multicultural prularis and even for the country consists of distinct ethnic, linguistic, religious, cultural, culture, and so forth. The diversity of culture is encapsulated in the motto Unity in Diversity, which means even different but still one. In the socio-historical, the presence of Islam in Indonesia can not be separated from a multicultural context as can be read in the history of Islam in the archipelago brought by Walisongo. Furthermore, making Islam multicultural topics or discourse is interesting and needs to be widely disseminated. This is at least three reasons. First, the circumstances of conflict. In the midst of circumstances that often conflict, multicultural Islam requires the establishment of the Islamic community who love peace, harmony and tolerance. Therefore, the goal to create and promote the establishment of the situation and the conditions of peace, order and harmony became an important agenda for the people of the world, including Indonesia. Second, the reality that diversity. The religions diversity, ethnic, ethnicity, and language becomes imperative to be addressed by all parties, especially the Muslim community in Indonesia. Therefore, social responsibility is not only on the government but also religious. In other words, peace-conflict societies also rely on contributions creation of a peaceful religious people, including the Muslims in this country. Robert N. Bellah, a sociologist of religion from the United States, said that through the Prophet Muhammad in Arabia, Islam has become a huge multicultural civilization, mighty and awesome to sur pass the greatness of the country the birth of Islam, the Arabian Peninsula. In this context, tolerance and mutual respect for religious differences, as revealed Wilfred Cantwell Smith, needs to be maintained and cultivated. Third, religious norms. As a noble teachings of religion would be a strong foundation for the clergy in general to create conditions so that no profanity. In this case, religious inter pretations is not expected based solely on the text, but also the context of that text can be captured according mean age meaning. The debate between the flow taaqquli are based on the power ratio/reason and the flow of taabbudi which relies on aspects of the text has been represented by two streams, namely Mutazilah and Ashariyah, the lessons of the past can be very interesting.